2015
DOI: 10.3389/fmicb.2015.00246
|View full text |Cite
|
Sign up to set email alerts
|

Enrichment experiment changes microbial interactions in an ultra-oligotrophic environment

Abstract: The increase of nutrients in water bodies, in particular nitrogen (N) and phosphorus (P) due to the recent expansion of agricultural and other human activities is accelerating environmental degradation of these water bodies, elevating the risk of eutrophication and reducing biodiversity. To evaluate the ecological effects of the influx of nutrients in an oligotrophic and stoichiometrically imbalanced environment, we performed a replicated in situ mesocosm experiment. We analyzed the effects of a N- and P-enric… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
34
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(42 citation statements)
references
References 83 publications
(120 reference statements)
8
34
0
Order By: Relevance
“…Therefore, we determined the antibiotic resistant profile of the 15 strains studied in this work against carbenicillin (500 μg/ml), tetracycline (150 μg/ml), kanamycin (200 μg/ml), streptomycin (200 μg/ml), chloramphenicol (200 μg/ml), gentamycin (150 μg/ml), and apramycin (100 μg/ml). In agreement with previous results for Pseudomonas isolated from the intermediate lagoon (Ponce-Soto et al, 2015), we found that the 15 analysed strains are resistant to carbenicillin and kanamycin and sensitive to the rest of the antibiotics tested. This, along with their unique phylogenetic position reinforces the idea of these two clonal groups being native to the Churince system.…”
Section: Resultssupporting
confidence: 92%
See 3 more Smart Citations
“…Therefore, we determined the antibiotic resistant profile of the 15 strains studied in this work against carbenicillin (500 μg/ml), tetracycline (150 μg/ml), kanamycin (200 μg/ml), streptomycin (200 μg/ml), chloramphenicol (200 μg/ml), gentamycin (150 μg/ml), and apramycin (100 μg/ml). In agreement with previous results for Pseudomonas isolated from the intermediate lagoon (Ponce-Soto et al, 2015), we found that the 15 analysed strains are resistant to carbenicillin and kanamycin and sensitive to the rest of the antibiotics tested. This, along with their unique phylogenetic position reinforces the idea of these two clonal groups being native to the Churince system.…”
Section: Resultssupporting
confidence: 92%
“…Many strains belonging to species of the fluorescent Pseudomonas isolated from the Churince system are unable to produce fluorescent siderophores even belonging to fluorescent Pseudomonas species (Escalante et al ., ; Toribio et al ., ; Bonilla‐Rosso et al ., ; Rodríguez‐Verdugo et al ., ; Ponce‐Soto et al ., ), and the same is true for P. aeruginosa strains isolated in 2011 (44 strains) and 2015 (5 strains) analysed in this work.…”
Section: Resultssupporting
confidence: 77%
See 2 more Smart Citations
“…In freshwater aquatic ecosystems, biochemical and elemental composition of natural seston fluctuates considerably and affects food web dynamics (sønDergaarD et al 1999;De senerPont Domis et al 2013), for instance via the microbial community (eLser et al 1995;cotner et al 2010;Ponce-soto et al 2015), but also via zooplankton performance in terms of reproduction, mortality, growth rate and community composition (sterner et al 1993;VerreyDt et al 2012;sarPe et al 2014). For instance, the keystone grazer Daphnia (Crustacea, Branchiopoda) requires a sufficient amount of P to invest in P-rich ribosomal RNA (rRNA), which is needed for protein synthesis and growth (eLser et al 2000(eLser et al , 2003.…”
Section: Introductionmentioning
confidence: 99%